EVALUATION OF THE GROUNDWATER QUALITY IN GISHIRI VILLAGE – KATAMPE, ABUJA USING WATER QUALITY INDEX - Jones, Emmanuel Ubong; Dandajeh, Aliyu Adamu; Shaibu-Imodagbe, Egbenya Musa; Igbebe, Samson (FUDMA Journal of Sciences, 2024)
Water quality is inherently linked with human health, poverty reduction, food security, livelihoods, preservation of ecosystems, economic growth, and social development of societies. This study evaluated the groundwater quality of Gishiri-Katampe, Abuja-Nigeria using statistical and geospatial techniques for water quality indexing. The study also used hydro-chemical parameters, geographical information, and statistical analysis to assess groundwater pollution potential; identify the most vulnerable areas, and generate a groundwater quality map. The Canadian Water Quality Index, the GIS mapping of the water quality of Gishiri indicates that the Water Quality Index is within the range of 76.87 to 92.53. Similarly, the WQI is predominantly good (62%), indicating a minor degree of threat. However, 38% of the area is occasionally threatened (fair) on the Canadian scale. However, some areas are occasionally threatened (fair) with the corresponding WQI of 28% within the study area. Moreover, out of the 11 water quality parameters analyzed, 6 parameters (dissolved oxygen DO, turbidity, chemical oxygen demand COD, NO3, Na, and biological oxygen demand BOD) were identified as significant parameters as indicated by the correlation and regression analysis. This suggested that they strongly influenced the variability of the water quality.
Keywords: Groundwater; Geospatial; Hydro-chemical parameters; Pollution; Water quality index